Manufacturing The Meiji Era : Portrayal of The Meiji Restoration in Kagoshima Museums and Heritage Sites - Sava, Ville (My University, 2021)
The passing of the 150th anniversary of the Meiji Restoration was commemorated in various parts of Japan in 2018, causing an upsurge in discussions regarding this historical event. This was especially visible in Kagoshima that was home to many of the leaders of the Meiji Restoration. Promoting itself as “The Home of the Meiji Restoration”, it hoped to capitalize on this anniversary by drawing in visitors to its historical sites and museums related to the Meiji Restoration and the surrounding events. This work’s objective is to find out and discuss what kind of portrayal two of the most popular history museums in Kagoshima, the Museum of the Meiji Restoration and Shōko Shūseikan Museum, offer of these events through their textual and audio-visual materials, and compare them to other narratives on these events and surrounding issues as presented by various sources both within and without Japan. The selection of these comparative sources includes speeches and discussions by Japanese government officials, academical works from both Japan and the West in addition to newspaper articles. This work also investigates motivations that drive Kagoshima to promote these sites and reinforce its connection to the developments surrounding the Meiji Restoration. For this purpose, documents plans from various departments of Kagoshima City has been utilized as well. As this work will show, the narrative of the two museums is rather conservative, and it is based on the traditional narratives of the Great Man Theory of History, assigning significant importance to the leaders that rose from Kagoshima in the events of the Meiji Restoration. Museums utilize this and other elements to build up national and local pride. It is a narrative that is mutually beneficial to the dominant Liberal Democratic Party and Kagoshima itself. It legitimizes preexisting institutions and power structures promoted by the Liberal Democratic Party, and elevates Kagoshima to a location of national relevance, while it and its museums remain financially dependent on funding from the central government.
Keywords: Japan, Meiji Restoration, Kagoshima, history, museum, narrative, portrayal